2022
DOI: 10.1093/geroni/igac056
|View full text |Cite
|
Sign up to set email alerts
|

Estimated Pulse Wave Velocity and All-Cause Mortality: Findings From the Health and Retirement Study

Abstract: Background and Objectives The gold standard method for the assessment of vascular aging is carotid-femoral pulse wave velocity (cfPWV). cfPWV can be estimated from two commonly assessed clinical variables—age and blood pressure. This analysis uses data from the Health and Retirement Study to examine the relationship between estimated pulse wave velocity (ePWV) and mortality among 9,293 middle-age and older adults. Research Design and Methods … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 51 publications
0
3
0
Order By: Relevance
“…Moreover, the group receiving intensive blood pressure therapy showed a notable decrease in the ePWV progression rate, leading to a relative reduction in cardiovascular event occurrence. Prospective cohort studies conducted across diverse racial populations have consistently demonstrated that the ePWV can serve as an independent prognostic indicator for overall mortality ( 18 20 ). Combined, these findings underscore the significance of ePWV as an autonomous predictor of cardiovascular events and mortality risk.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, the group receiving intensive blood pressure therapy showed a notable decrease in the ePWV progression rate, leading to a relative reduction in cardiovascular event occurrence. Prospective cohort studies conducted across diverse racial populations have consistently demonstrated that the ePWV can serve as an independent prognostic indicator for overall mortality ( 18 20 ). Combined, these findings underscore the significance of ePWV as an autonomous predictor of cardiovascular events and mortality risk.…”
Section: Resultsmentioning
confidence: 99%
“…The ePWV only requires age and average blood pressure to easily obtain results. Recently, ePWV has been shown to be an independent predictor of cardiovascular disease events and survival status (17)(18)(19)(20)(21)(22)(23)(24). However, whether ePWV can independently predict cardiovascular and all-cause mortality in Chinese patients with hypertension and whether it is superior to baPWV in predicting mortality remains unclear.…”
Section: Introduction Backgroundmentioning
confidence: 99%
“…Studies have demonstrated a correlation between ePWV and established markers of vascular aging, including carotid thickness, carotid stiffness and augmentation dilatation index [42]. Although ePWV cannot completely replace cfPWV to assess arterial stiffness, ePWV has been shown to provide a robust predictive value as a 'gatekeeper' for all-cause mortality in different cohorts [43][44][45]. Laugesen et al [46] observed 25,066 patients with stable angina for 8.5 years and found a 13% increase in the risk of all-cause mortality with a 1 m/s increase in ePWV levels.…”
Section: Antihypertensivesmentioning
confidence: 99%
“…However, there is still controversy over whether the association between ePWV and adverse clinical outcomes is independent of traditional cardiovascular risk estimation model or risk factors. Previous researches aiming in this issue either excluded the CVDs population [ 16 , 17 ] or conducted in specific population with increased cardiovascular risk [ 15 , 18 ] or established CVDs [ 19 ]. Thus, it is not yet known whether their conclusions can be extrapolated to the general population.…”
Section: Introductionmentioning
confidence: 99%